Rheological Behavior of Renewable Polyethylene (HDPE) Composites and Sponge Gourd (Luffa cylindrica) Residue - Viviane Alves Escócio; Elen Beatriz Acordi Vasques Pacheco; Ana Lucia Nazareth da Silva; André de Paula Cavalcante; Leila Léa Yuan Visconte (International Journal of Polymer Science)
The present study reports the results of rheological behavior of renewable composites, based on a matrix of high density polyethylene (HDPE), made from ethanol distilled from sugarcane, and lignocellulose filler from waste generated in the processing of sponge gourds for bathing use. The composites were prepared with 10, 20, 30, and 40%wt of filler in a twin-screw extruder. The materials were analyzed in a parallel plate rheometer and a melt-flow indexer. The composite morphology was determined by scanning electron microscopy. The composite viscosity increased with filler content, suggesting possible formation of filler agglomerates. This result was confirmed by Cole-Cole diagrams.